Habitat loss, climate change, and emerging conservation challenges in Canada 1 This review is part of the virtual symposium “Flagship Species – Flagship Problems” that deals with ecology, biodiversity and management issues, and climate impacts on species at risk and of Canadian importance, including the polar bear ( Ursus maritimus), Atlantic cod ( Gadus morhua), Piping Plover ( Charadrius melodus), and caribou ( Rangifer tarandus). - Coristine, Laura E.; Kerr, Jeremy T. (Canadian Journal of Zoology, 2011)
In Canada, habitat loss has pushed many more species to the brink of extinction than expected in a region with extensive wilderness. However, species richness gradients depend strongly on climate, so species are concentrated in southern regions, where agricultural and urban land uses are both intensive and extensive. Agricultural pesticide use is associated with increasing rates of species endangerment in the south, but long-range transport of persistent organic pollutants is an emerging issue in remote northern regions. Because their distributions reflect climate so strongly, climate change threatens species throughout Canada. Evidence indicates that species’ distributions, phenologies, and interactions with pests and diseases are changing more rapidly in response to climate change than global mean values. Nevertheless, climate change is expected to impose dispersal requirements that surpass species’ maximum rates. Habitat losses may interact with climate change to impair species’ dispersal still further, creating the potential for widespread disruption of biological systems in the most diverse areas of Canada. New research is urgently needed to address questions, and the ethics, around species translocation, ecosystem engineering to anticipate future environmental conditions, and strategies to facilitate the persistence of rare species in landscapes dominated by human activities.